Incidence of Work and Workplace Injury Among Alberta Teens - Barnetson, Bob (Just Labour, 2013)
Utilizing a convenience sample of nearly 2000 respondents drawn from administrative data, this study finds 43.7 percent of adolescents (aged 12-14) and 61.5 percent of young persons (aged 15-17) in the Canadian province of Alberta reported employment in 2011/12. Of those employed, 49.7 percent of adolescents and 59.0 percent of young persons reported at least one work-related injury in the previous year. This study also identifies widespread non-reporting of workplace injuries and seemingly ineffective hazard identification and safety training. These results add to the growing evidence that the regulation of teenage employment in Alberta fails to adequately protect these workers from injury.